Head teachers and students opinions about classroom factors that affect performance of students in integrated science at the Junior High Schools in Kumasi Metropolis - Amoah, Charles Agyei; Owusu, Michael; Teye Nartey, Laud; Akwasi Frimpong, Richard (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study is to find out the opinions of head teachers and students on classroom factors that affect performance of students in integrated science at the Junior High Schools in Kumasi Metropolis. The study used a descriptive survey. The sampling procedure employed for the study was both random and purposive sampling. A sample of two hundred and twenty (220) subjects participated in the study. The instruments that were used in the study were questionnaire and interview schedule. It was found out that most of the students in the public schools have greater access to integrated science text books as against their private school counterparts. Supervision is regularly carried out in the private schools by the head teachers but not much can be seen at the public schools and this has the tendency of improving teaching and learning of science at the private school. It was recommended that effective supervision must be performed regularly by heads of schools during integrated science lessons.